Multi‐level gene expression signatures, but not binary, outperform Ki67 for the long term prognostication of breast cancer patients. Issue 3 (28th February 2014) - Tobin, Nicholas P.; Lindström, Linda S.; Carlson, Joseph W.; Bjöhle, Judith; Bergh, Jonas; Wennmalm, Kristian
Abstract : Proliferation‐related gene signatures have been proposed to aid breast cancer management by providing reproducible prognostic and predictive information on a patient‐by‐patient basis. It is unclear however, whether a less demanding assessment of cell division rate (as determined in clinical setting by expression of Ki67) can function in place of gene profiling. We investigated agreement between literature‐, distribution‐based, as well as signature‐derived values for Ki67, relative to the genomic grade index (GGI), 70‐gene signature, p53 signature, recurrence score (RS), and the molecular subtype models of Sorlie, Hu, and Parker in representative sets of 253 and 159 breast cancers with a median follow‐up of 13 and 14.5 years, respectively. The relevance for breast cancer specific survival was also addressed in uni‐ and bivariate Cox models. Taking both cohorts into account, our broad approach identified ROC optimized Ki67 cutoffs in the range of 8–28%. With optimum signature‐reproducing cutoffs, similarity in classification of individual tumors was higher for binary signatures (72–85%), than multi‐level signatures (67–73%). Consistent with strong agreement, no prognostic superiority was noted for either Ki67 or the binary GGI, 70‐gene and p53 signatures in the Uppsala dataset by bivariate analyses. In contrast, Ki67‐independent prognostic capacity could be demonstrated for RS and molecular subtypes according to Sorlie, Hu and Parker in both datasets. Our results show that the added prognostic value of binary proliferation‐related gene signatures is limited for Ki67‐assessed breast cancers. More complex, multi‐level descriptions have a greater potential in short‐ and long‐term prognostication for biologically relevant breast cancer subgroups. Highlights: Patient survival within gene expression signature subtypes can vary greatly over time. Ki67 and binary gene expression signatures similarly classify breast cancer patients. Multi‐level gene expression signatures outperform Ki67 for patient prognosis.